Respuesta :
Answer:
4(−3)2
Step-by-step explanation:
The common factor ) 42−24+36, 4(2−6+9)
Sum-product pattern ) 4(2−6+9) 4(2−3−3+9)
Common factor from the two pairs we did) 4(2−3−3+9) 4((−3)−3(−3))
Rewrite into factors ) 4((−3)−3(−3)) 4(−3)(−3)
Lastly, combine to a square.) 4(−3)(−3) 4(−3)2
I hope this helps you; g'day!
Given equation is 4x²-24x-36 = 0
⇛ 4(x²-6x-9) = 0
⇛ x²-6x-9 = 0
⇛ x²-2(x)(3) = 9
On adding 3² both sides then
⇛ x²-2(3)x)+3² = 9+9
⇛ (x-3)² = 18
⇛ (x-3) = ±√18
⇛ x-3 = ±√(2×9)
⇛ x-3 = ±3√2
⇛ x = 3±3√2
⇛ x = 3+3√2 or 3-3√2 Ans.